2007
DOI: 10.1111/j.1524-475x.2006.00187.x
|View full text |Cite
|
Sign up to set email alerts
|

Streptolysin O enhances keratinocyte migration and proliferation and promotes skin organ culture wound healing in vitro

Abstract: ML-05, a modified form of the hemolytic and cytotoxic bacterial toxin, streptolysin O, is currently being investigated as a treatment for collagen-related disorders such as scleroderma and fibrosis. Furthermore, ML-05 may be effective in promoting wound healing and alleviating the formation of hypertrophic scars and keloids. To investigate the effects of ML-05 on wound-healing processes, in vitro wound-healing scratch assays (using human primary epidermal keratinocytes and dermal fibroblasts) and a human skin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 52 publications
(139 reference statements)
0
36
0
Order By: Relevance
“…Our study demonstrated profound downregulation of Smad7 in the basal layer of the epidermis of VUs, whereas Smad7 was upregulated in keratinocytes of acute wounds ex vivo. The human skin organ culture model has been extensively and reliably used to study epidermal wound healing (33)(34)(35)(36)(37)62); however, it was never used to analyze TGFβ signaling. Showing induction of Smad2 phosphorylation and upregulation Smad7, we confirmed activation of TGFβ signaling in an acute ex vivo wound model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study demonstrated profound downregulation of Smad7 in the basal layer of the epidermis of VUs, whereas Smad7 was upregulated in keratinocytes of acute wounds ex vivo. The human skin organ culture model has been extensively and reliably used to study epidermal wound healing (33)(34)(35)(36)(37)62); however, it was never used to analyze TGFβ signaling. Showing induction of Smad2 phosphorylation and upregulation Smad7, we confirmed activation of TGFβ signaling in an acute ex vivo wound model.…”
Section: Discussionmentioning
confidence: 99%
“…Healthy skin samples were used to generate acute wounds as previously described (30)(31)(32)(33). Ex vivo human experimental wound models have been extensively used to study wound healing in human skin.…”
Section: Human Skin Ex Vivo Wound-healing Modelmentioning
confidence: 99%
“…Interestingly, ligand-activated Ser 211 -phosphorylated-GR (GR-P) was localized in the nuclei of epidermal keratinocytes, suggesting endogenous hormone-induced activation of the receptor. To analyze the activity of the GC pathway in isolated epidermis without an external source of GCs, we incubated normal human skin on an air-liquid interface in basal, serum-free medium (40) in the absence of hydrocortisone for 24 h. Skin specimens were stained with GR-P antibody, and the signal was found in more than 30% of the nuclei of the cells in the epidermis of untreated human skin (Fig. 1A).…”
Section: Resultsmentioning
confidence: 99%
“…Cortisol Production Is Regulated during Acute Wound Healing-To further understand GC synthesis during wound healing, we used an established ex vivo human skin organ culture wound model (40). Acute wounds were maintained for 0, 4, 24, 48, and 96 h post wounding at the air-liquid interface, and the expression level of CYP11B1 was determined using realtime qPCR.…”
Section: Cyp11b1 An Enzyme Responsible For the Finalmentioning
confidence: 99%
“…Wounds were created using 3-mm punch biopsies through the reticular dermis as previously described (29). They were maintained at the air-liquid interface using Dulbecco's modified Eagle's medium (Invitrogen) with antibiotics and antimycotics and stripped bovine serum.…”
Section: Methodsmentioning
confidence: 99%